2018
DOI: 10.1016/j.mvr.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

YAP1-TEAD1 signaling controls angiogenesis and mitochondrial biogenesis through PGC1α

Abstract: Mitochondria contribute to key processes of cellular function, while mitochondrial dysfunction is implicated in metabolic disorders, neurodegenerative diseases, and cardiovascular diseases, in which angiogenesis - the formation of new blood capillaries - is dysregulated. The Hippo signaling transducer, Yes-associated protein (YAP1) binds to the TEA domain (TEAD1) transcription factor and controls angiogenesis. YAP1 also regulates glucose metabolism through peroxisome proliferator-activated receptor gamma co-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 88 publications
2
49
0
Order By: Relevance
“…Besides the VEGF signaling axis, YAP regulates angiogenesis via the peroxisome proliferator-activated receptor gamma co-activator 1-alpha (PGC1α) signaling pathway that controls glucose metabolism within the mitochondria of ECs ( Mammoto et al, 2018 ). Mammoto et al (2018) showed that PGC1α knockdown inhibits YAP-induced EC sprouting in vitro and vascular morphogenesis within fibrin gels subcutaneously implanted into mice, whereas overexpression of PGC1α had the reverse effect. Hence, YAP-TEAD1 signaling induces mitochondrial biogenesis in ECs and stimulates angiogenesis through PGC1α.…”
Section: Modulation Of Stem/progenitor Cell Lineage Fate By Yap/tazmentioning
confidence: 99%
“…Besides the VEGF signaling axis, YAP regulates angiogenesis via the peroxisome proliferator-activated receptor gamma co-activator 1-alpha (PGC1α) signaling pathway that controls glucose metabolism within the mitochondria of ECs ( Mammoto et al, 2018 ). Mammoto et al (2018) showed that PGC1α knockdown inhibits YAP-induced EC sprouting in vitro and vascular morphogenesis within fibrin gels subcutaneously implanted into mice, whereas overexpression of PGC1α had the reverse effect. Hence, YAP-TEAD1 signaling induces mitochondrial biogenesis in ECs and stimulates angiogenesis through PGC1α.…”
Section: Modulation Of Stem/progenitor Cell Lineage Fate By Yap/tazmentioning
confidence: 99%
“…A luciferase reporter assay revealed binding sites for miR-520d-5 on TEA domain transcription factor 1 (TEAD1) target gene [86]. It has been proven recently that knockdown of TEAD1 decreases the expression of PGC1α and suppresses mitochondrial biogenesis, glycolysis, and oxygen consumption in endothelial cells [87]. Reducing the number of active mitochondria and slowing down the rate of mitochondrial oxidation as a result of down-regulation of TEAD1 and PGC1-α may contribute to disturbed fatty acid catabolism, and consequently to the development of fatty liver in high GIP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate physical properties of lung tissue are necessary for physiological postnatal lung development and LRP5 signaling mediates ECM structure-dependent angiogenesis and alveolar morphogenesis in the neonatal mouse lung [17]. Other mechanosensitive transcription factors and co-activators (e.g., TFII-I, GATA2, Twist1, YAP1) also control angiogenesis [43,48,73,76], and contribute to lung diseases ( e.g., pulmonary fibrosis, pulmonary hypertension) [42,43,77]. Aged fibroblasts produce more collagen and less elastin, leading to increasing pulmonary stiffness and lowering compliance [78].…”
Section: Discussionmentioning
confidence: 99%